If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2f(3f + -5) = 0 Reorder the terms: -2f(-5 + 3f) = 0 (-5 * -2f + 3f * -2f) = 0 (10f + -6f2) = 0 Solving 10f + -6f2 = 0 Solving for variable 'f'. Factor out the Greatest Common Factor (GCF), '2f'. 2f(5 + -3f) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'f' equal to zero and attempt to solve: Simplifying f = 0 Solving f = 0 Move all terms containing f to the left, all other terms to the right. Simplifying f = 0Subproblem 2
Set the factor '(5 + -3f)' equal to zero and attempt to solve: Simplifying 5 + -3f = 0 Solving 5 + -3f = 0 Move all terms containing f to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3f = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3f = 0 + -5 -3f = 0 + -5 Combine like terms: 0 + -5 = -5 -3f = -5 Divide each side by '-3'. f = 1.666666667 Simplifying f = 1.666666667Solution
f = {0, 1.666666667}
| 25=10+ | | 10x^2+14x+3=0 | | y=2-lx+1l | | 34=4x-6 | | -149=x^2-24x | | -2(45-5)-10=-3 | | 31=5x+1 | | x^2+2x+3=18 | | 0.75q=24 | | P=1+0.03x | | 9x+4=9(x+4) | | X-20=X | | 2a-3a=7 | | 13x=46 | | 0.25x-0.4=1.6 | | D=40-15x | | 2x+8x+15=0 | | 5X-5-40=4X-16 | | 3(2x-1)+3=2(x-5) | | 2x^4-2x^3+4x^2+3x-7=02 | | 3(4y-9)=12 | | 12(x-1)=6x+36 | | x^5+x^4-2x^3+4x^2+3x-7=0 | | x^500+7=0 | | x/18+=-2 | | 5-2x-8x-7=8-8x | | 5x-3y= 56 | | 4x-24=-2x+6 | | C+9=2c+5 | | y-7=3(x-4) | | 4y=-9x+10 | | 4+6s-1=7s+15-5s |